PENDIDIKAN DASAR ISLAM BERBASIS RAHMATAN LIL-ALAMIN - Ikhsan, Moh Hayatul (INCARE, International Journal of Educational Resources, 2024)
Islamic primary education plays a crucial role in shaping the moral and social character of children, particularly in facing the challenges of globalization and modernization that are increasingly developing. This article aims to examine the role of Islamic primary education based on the concept of rahmatan lil-alamin as a solution to address moral and social issues in a pluralistic society. The research method used in this study is a literature review with a qualitative approach, linking various theories of Islamic education and social construction. The results of the study indicate that Islamic primary education based on rahmatan lil-alamin can develop a character that is tolerant, open-minded, and appreciative of diversity, as well as prevent radicalization and intolerance in society. This education also serves as a moral fortress and a tool to build peace and interfaith harmony. Therefore, Islamic primary education based on rahmatan lil-alamin has great potential to create a more harmonious, civilized, and inclusive society.